The V4 and European Integration - Bauerová Helena (Sciendo, 2018)
The activities of the Visegrad Group countries in the EU have clearly demonstrated a range of themes that Member States are willing to address on a common platform. The chapter analyzes the extent to which the V4 countries are able to seek common interest, which is subsequently presented as a common position representing V4 interest at EU level. The analysis is based on the presidency of the Visegrad Group countries in the EU. The Presidency will be analyzed in view of the merging of the interests between the Visegrad Group and EU policies. In particular, energy policy, enlargement policy and neighborhood policy were chosen plus the partial policies influenced by the integration process at the time, such as migration policy or quota system issues.